Agroecological production of quinoa native ecotypes of colors (Chenopodium quinoa Willd.) with effective microorganisms - Palao Iturregui, Luis Alfredo (2019)
University of the Altiplano, located in the district of Paucarcolla province and Region Puno, located at 3850 m.a.s.l. The aim of this research was to evaluate the agroecological production of quinoa ecotypes of colors (Chenopodium quinoa Willd.) by the use of Effective Microorganisms (EM); to evaluate the physical and chemical characteristics of the soil at the beginning and end of the experiment; to characterize the pigments of the quinoa ecotypes and compare production costs. The experiment was conducted under a randomized complete block design with a factorial arrangement of 9 x 3 x 2, of nine quinoa ecotypes, three doses of EM and two agroecological practices (organic matter and ornithological control) with 54 treatments in 3 blocks and a total of 162 experimental units. The soil analyzes were performed by routine procedures, the microbiological analysis was carried out by counting in colony forming units. The best grain yield was with the Black Collana ecotype with 3072.17 kg / ha, with the dose of 15% of EM and agro-ecological applications. There was a significant increase in soil microbiology at the end of the growing period, in aerobic bacteria, yeasts, molds, lactobacillus and actinomycetes. The characterized pigments were betacyanines (red to violet) and betaxanthins (yellow to orange) with a predominance of 150 to 159 codings. The Black Collana and Mistura ecotypes, with 15% EM doses and agroecological applications had higher net profits, profitability and B/C ratio.